2016
DOI: 10.1093/ehjci/jew101
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and prognostic utility of cardiovascular magnetic resonance imaging in myeloma patients with suspected cardiac amyloidosis

Abstract: CMR is a clinically useful tool for diagnosis and prognostication in myeloma patients with suspected CA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 27 publications
1
24
0
2
Order By: Relevance
“…Of the 2947 studies, we identified 27 meeting the inclusion criteria, including data on 3493 patients ( Figure ). Twenty‐two studies evaluated the performance of CMR in diagnosing either cardiac amyloidosis or ATTR amyloidosis, with a further five studies assessing the diagnostic performance of nuclear scintigraphy . Seventeen studies assessing the performance of index tests in the diagnosis of cardiac amyloidosis included patients with a range of cardiac conditions, whereas 9 out of 11 studies diagnosing ATTR amyloidosis included patients with ATTR or AL amyloidosis only.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 2947 studies, we identified 27 meeting the inclusion criteria, including data on 3493 patients ( Figure ). Twenty‐two studies evaluated the performance of CMR in diagnosing either cardiac amyloidosis or ATTR amyloidosis, with a further five studies assessing the diagnostic performance of nuclear scintigraphy . Seventeen studies assessing the performance of index tests in the diagnosis of cardiac amyloidosis included patients with a range of cardiac conditions, whereas 9 out of 11 studies diagnosing ATTR amyloidosis included patients with ATTR or AL amyloidosis only.…”
Section: Resultsmentioning
confidence: 99%
“…Among the four studies using nuclear scintigraphy to differentiate ATTR from AL amyloidosis, three studies specified a monoclonal protein screen in the methodology, the complete results of which were available in only one study . Among 11 studies using EMB as the reference test, five obtained tissue samples from the right ventricle and one involved biventricular EMB; the remaining studies did not report on EMB technique. One study reported no complications following EMB in all subjects, whereas others did not comment on the incidence of complications.…”
Section: Resultsmentioning
confidence: 99%
“…The gold standard for diagnosing cardiac amyloidosis is endomyocardial biopsy, but noninvasive cardiac imaging can replace the need for cardiac biopsy. Cardiac MRI late gadolinium enhancement was shown to be highly sensitive (80–100%) with a negative predictive value of 85–100%, while the specificity and positive predictive values are 80–94 and 81–92%, respectively [17, 18]. Cardiac MRI is unable to reliably differentiate between the various subtypes of cardiac amyloidosis.…”
Section: Diagnosis and Typingmentioning
confidence: 99%
“…In contrast to echocardiography, cardiac magnetic resonance imaging (CMR) is not dependent on good acoustic windows, has higher spatial resolution, and provides tissue characterization. Studies have shown that certain late gadolinium enhancement (LGE) patterns on CMR are highly sensitive and specific for CA and may even precede morphologic increases in LV wall thickness [26]. Gadolinium contrast agents preferentially distribute in the extracellular space.…”
Section: Cardiac Magnetic Resonance Imagingmentioning
confidence: 99%